2018
DOI: 10.1177/2309499018802429
|View full text |Cite
|
Sign up to set email alerts
|

Higher body mass index is not a risk factor for in-hospital adverse outcomes following total knee arthroplasty

Abstract: Purpose: To investigate the association between body mass index (BMI) and perioperative complications until hospital discharge, following primary total knee arthroplasty (TKA). Methods: This retrospective study reviewed 1665 cases of elective primary unilateral TKA performed between 2006 and 2010, from a prospective secure electronic database. Types of complications, length of operating time, and duration of hospital stay were analyzed in both adjusted (for known confounders) and unadjusted analyses. A further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(33 reference statements)
0
5
0
3
Order By: Relevance
“…One additional article was identified from citation search and 210 full‐text articles were assessed for eligibility. Finally, 91 studies were included, with 22 prospective, 4,7,8,16,22–39 54 retrospective, 6,9–12,14,15,17,40–85 and 15 case‐controlled studies 5,13,18,19,86–96 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One additional article was identified from citation search and 210 full‐text articles were assessed for eligibility. Finally, 91 studies were included, with 22 prospective, 4,7,8,16,22–39 54 retrospective, 6,9–12,14,15,17,40–85 and 15 case‐controlled studies 5,13,18,19,86–96 …”
Section: Resultsmentioning
confidence: 99%
“…However, literature on TKA complications in the obese population has been inconsistent. Some studies revealed that obese TKA patients had higher peri‐operative complication rates, 4–9 while others reported similar complication and revision rates 10–15 . With the rising severity of obesity globally, the implications of morbid (BMI ≥ 40 kg/m 2 ) and super obesity (BMI ≥ 50 kg/m 2 ) on TKA outcomes is of research interest 16–19 .…”
Section: Introductionmentioning
confidence: 99%
“…Очевидно, что такие пациенты чаще страдают патологией крупных суставов нижних конечностей, которая прогрессирует уже в молодом возрасте [9,10]. Ожи-рение является условным ограничением для проведения планового эндопротезирования, поскольку в ряде случаев приводит к послеоперационным осложнениям, но специалисты сходятся во мнении, что оно необходимо для повышения качества жизни этой группы пациентов [11][12][13][14].…”
Section: Conclusion the Study Results Demonstrate The High Potentialunclassified
“…Длительность оперативного вмешательства у пациентов с повышенным ИМТ оказалась предсказуемо выше, чем в группе сравнения. Эти данные согласуются с мнением австралийских коллег [14], отметивших значительное увеличение времени вмешательства у пациентов с повышенным ИМТ. Однако работа на коленном суставе у «тучных» пациентов оказалась явно проще, чем в случаях эндопротезирования тазобедренного сустава.…”
Section: Discussionunclassified
See 1 more Smart Citation